2011
DOI: 10.5206/wurjhns.2010-11.2
|View full text |Cite
|
Sign up to set email alerts
|

Trunk Extensor Muscle Fatigue Does Not Affect Postural Control during Upright Static Stance in Young-adults and Middle-aged Adults

Abstract: Background. Falls can be extremely detrimental to someone’s daily living, as well as life threatening This is especially true for individuals who have back problems, are sedentary, and have other health disorders. The purpose of this study was to investigate the effect of trunk extensor muscles fatigue on static postural control in young healthy adults compared to middle aged subjects. Methods. University students (n=10), and Middle-aged subjects (n=6; 40+ years of age) stood as immobile as possible on a forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…There is substantial evidence on the detrimental effect of fatigue on postural control in older adults [6]. However previous research on healthy young adults has been inconsistent as some studies have shown that postural control in quiet standing and during various dynamic perturbations can be maintained during muscle fatigue [18,19]. Muscle fatigue has been proposed to cause a change in postural control strategy and several researchers have posited that changes in postural control do not necessarily imply a decrease in postural stability [17].…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence on the detrimental effect of fatigue on postural control in older adults [6]. However previous research on healthy young adults has been inconsistent as some studies have shown that postural control in quiet standing and during various dynamic perturbations can be maintained during muscle fatigue [18,19]. Muscle fatigue has been proposed to cause a change in postural control strategy and several researchers have posited that changes in postural control do not necessarily imply a decrease in postural stability [17].…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence on the detrimental effect of fatigue on postural control in older adults [6]. However previous research on healthy young adults has been inconsistent as some studies have shown that postural control in quiet standing and during various dynamic perturbations can be maintained during muscle fatigue [18,19]. Muscle fatigue has been proposed to cause a change in postural control strategy and several researchers have posited that changes in postural control do not necessarily imply a decrease in postural stability [17].…”
Section: Introductionmentioning
confidence: 99%
“…6 However previous research on healthy young adults has been inconsistent as some studies have shown that postural control in quiet standing and during various dynamic perturbations can be maintained during muscle fatigue. 18,19 Muscle fatigue has been proposed to cause a change in postural control strategy and several researchers have posited that changes in postural control do not necessarily imply a decrease in postural stability. 17 Most of the investigations cited above referred to postural control following lower limb efforts or general body fatigue.…”
Section: Introductionmentioning
confidence: 99%